A Comprehensive Systematic Review and Meta‐Analysis on the Prevalence of Aflatoxin M1 in Dairy Products in Selected Middle East Countries - Bahareh Arghavan; Kosar Kordkatuli; Helia Mardani; Ali Jafari (Veterinary Medicine and Science)
ABSTRACT Background Human consumption of dairy products contaminated with aflatoxin (AF) M1 can lead to severe health issues. This AF's significance and impact on health necessitate a thorough investigation of its prevalence in dairy products. Objectives This study aims to determine the prevalence of AFM1 in dairy products through a systematic review and meta‐analysis, focusing on data from Middle Eastern countries. Methods We identified relevant studies through electronic database searches (PubMed, Scopus and Web of Science) up to August 2023. We employed a random‐effects model to derive an overall estimate and used 95% confidence intervals to determine pooled prevalence rates. Results The meta‐analysis included 193 studies encompassing 297,530 samples of dairy products. The results showed that AFM1 contaminated 87% of dairy products. The following is a ranking of countries based on the prevalence of AFM1 in their dairy products: Iran > Jordan > Turkey > Kuwait > Lebanon > Syria > Egypt > Cyprus > the United Arab Emirates. The current meta‐analysis indicated that Middle Eastern countries exhibited a high prevalence of AFM1 in dairy products. The prevalence rates for AFM1 in various dairy products were as follows: milk (87%), yogurt (68.9%), cheese (63.6%), kashk (62.9%), doogh (55.6%) and ice cream (54%). Pasteurized milk (99.5%), ultra‐high temperature (91.3%), raw milk (73%) and traditional milk (51%), among other milk types, had the highest contamination rates. Conclusion The study reveals a high prevalence of AFM1 in dairy products, particularly in Middle Eastern countries. Given the critical importance of milk and dairy products in the diet, special measures are needed to safeguard their quality and protect consumers from AF contamination.